Implementasi Pembelajaran Media Flip Chart dan Powerpoint Materi Dinamika Planet Bumi Sebagai Ruang Kehidupan Kelas X IPS 1 Dan X IPS 2 Ma Al-Asror Semarang - Astutik, Sri Dewi; Sriyanto, Sriyanto (Edu Geography, 2019)
Background of this research is the number of students who scored below KBM (72), that is 54% (15 of 28) students. The aim of this study are (1) to know the implementation of flip chart and powerpoint media (2) to find out the effectiveness of flip chart and powerpoint media which includes the achievement of completeness of student learning outcomes, student learning activities and student responses or positive responses. The population of this study was class X IPS 1 and X IPS 2. The sampling technique used was purposing sampling. The sample of this study is class X IPS 2 because in this class, many students had scores under KBM on the previous test. Data collection technique that used is documentation, observation, tests, and questionnaires. The data analysis technique that usedis descriptive percentage analysis and statistical analysis of the two-mean difference test (t-test). The results of the study show that the implementation of the teacher's ability to use flip chart and powerpoint media is in the good criteria. The assessment of the RPP of the both classes received 69 score or 81.18% and the implementation of learning in class X IPS 1 got 72 score or 80% meanwhile the class X IPS 2 got 73 score or 81.11%. Penelitian ini dilatarbelakangi oleh banyaknya siswa yang mendapat nilai di bawah KBM (72) yaitu 54% (15 dari 28) siswa. Tujuan penelitian ini adalah (1) mengetahui implementasi media flip chart dan powerpoint (2) mengetahui efektivitas media flip chart dan powerpoint yang meliputi ketercapaian ketuntasan hasil belajar siswa, aktivitas belajar siswa dan respon atau tanggapan positif siswa. Populasi penelitian ini kelas X IPS 1 dan X IPS 2. Teknik sampel yang digunakan purposing sampling. Sampel penelitian ini kelas X IPS 2 karena banyak siswa yang nilai ulangannya di bawah KBM. Teknik pengumpulan data menggunakan dokumentasi, observasi, tes, dan kuesioner. Teknik analisis data menggunakan analisis deskriptif persentase dan analisis statistik uji perbedaan dua ratarata (uji t-test). Hasil penelitian implementasi kemampuan guru dalam menggunakan media flip chart dan powerpoint termasuk dalam kriteria “baik”. Penilaian RPP kedua kelas mendapat skor 69 atau 81,18% dan pelaksanaan pembelajaran kelas X IPS 1 mendapat skor 72 atau 80% sedangkan kelas X IPS 2 mendapat skor 73 atau 81,11%.